Altered DNA Methylation in the Developing Brains of Rats Genetically Prone to High versus Low Anxiety - Chelsea R. McCoy; Matthew E. Glover; Leigh T. Flynn; Rebecca K. Simmons; Joshua L. Cohen; Travis Ptacek; Elliot J. Lefkowitz; Nateka L. Jackson; Huda Akil; Xiaowei Wu; Sarah M. Clinton (2019)
There is growing evidence of abnormal epigenetic processes playing a role in the neurobiology of psychiatric disorders, although the precise nature of these anomalies remains largely unknown. To study neurobiological (including epigenetic) factors that influence emotionality, we use rats bred for distinct behavioral responses to novelty. Rats bred for low novelty response (low responder [LR]) exhibit high levels of anxiety- and depressive-like behavior compared with high novelty responder (HR) rats. Prior work revealed distinct limbic brain development in HR versus LR rats, including altered expression of genes involved in DNA methylation. This led us to hypothesize that DNA methylation differences in the developing brain drive the disparate HR/LR neurobehavioral phenotypes. Here we report altered DNA methylation markers (altered DNA methyltransferase protein levels and increased global DNA methylation levels) in the early postnatal amygdala of LR versus HR male rats. Next-generation sequencing methylome profiling identified numerous differentially methylated regions across the genome in the early postnatal HR/LR amygdala. We also contrasted methylation profiles of male HRs and LRs with a control rat strain that displays an intermediate behavioral phenotype relative to the HR/LR extremes; this revealed that the LR amygdalar methylome was abnormal, with the HR profile more closely resembling that of the control group. Finally, through two methylation manipulations in early life, we found that decreasing DNA methylation in the developing male and female amygdala improves adult anxiety- and depression-like behavior. These findings suggest that inborn DNA methylation differences play important roles in shaping brain development and lifelong emotional behavior. SIGNIFICANCE STATEMENT Epigenetic changes are biological mechanisms that regulate the expression and function of genes throughout the brain and body. DNA methylation, one type of epigenetic mechanism, is known to be altered in brains of psychiatric patients, which suggests a role for DNA methylation in the pathogenesis of psychiatric disorders, such as depression and anxiety. The present study examines brains of rats that display high versus low levels of anxiety- and depression-like behavior to investigate how neural DNA methylation levels differ in these animals and how such differences shape their emotional behavioral differences. Studying how epigenetic processes affect emotional behavior may improve our understanding of the neurobiology of psychiatric disorders and lead to improved treatments.